Photography Poetry as A Hybrid Art Work - Nugroho, Yulius Widi (Journal of Urban Society's Arts, 2024)
Photography Poetry is a form of creative expression that combines literary and visual elements to create powerful and inspiring works of art. This research develops an art creation method using photography media to explore meaning directed towards poetry literary works, as a manifestation of the potential of poetry photography as a hybrid work of art. This creation aims to explore the process of making poetry photography, explore how to compose poetry words based on the visual elements of photography, and analyze how poetry photography works can be understood and enjoyed by the audience. Explore and develop methods used in creating hybrid works of art, using Roland Barthes’ theory of visual meaning. Producing unique and profound works of art, which are able to communicate meaning and emotion in a more complex way than words or images alone. An in-depth analysis of the results of the creation of this work reveals that poetry photography is a medium that allows artists to convey emotional and intellectual messages in a deeper and broader way. Poetic photography shows that hybrid art is a bridge between different types of creative expression, creating engaging experiences and changing the way we view art in a broader context. It is hoped that this research will become a basis for further development in the field of artistic and literary photography, as well as inspiring artists/researchers to continue exploring the boundaries of creativity in poetry photography. Fotografi Puisi merupakan bentuk ekspresi kreatif yang menggabungkan unsur-unsur sastra dan visual untuk menciptakan karya seni yang kuat dan menginspirasi. Penelitian ini mengembangkan metode penciptaan seni menggunakan media fotografi untuk menggali pemaknaan yang diarahkan untuk karya sastra puisi, sebagai wujud potensi fotografi puisi sebagai karya seni hibrida. Penciptaan ini bertujuan untuk menjelajahi proses pembuatan fotografi puisi, mengeksplorasi cara menyusun kata-kata puisi berdasarkan elemen visual fotografi, serta menganalisis bagaimana karya fotografi puisi dapat dipahami dan dinikmati oleh penonton. Menggali dan mengembangkan metode yang digunakan dalam menciptakan karya seni hibrida, menggunakan teori pemaknaan visual dari Roland Barthes. Menghasilkan karya-karya seni yang unik dan mendalam, yang mampu mengkomunikasikan makna dan emosi dengan cara yang lebih kompleks daripada kata-kata atau gambar sendiri. Analisis mendalam terhadap hasil penciptaan karya ini mengungkapkan bahwa fotografi puisi merupakan medium yang mampu memungkinkan seniman untuk menyampaikan pesan emosional dan intelektual dengan cara yang lebih mendalam dan luas. Fotografi puisi menunjukkan bahwa seni hibrida adalah jembatan antara berbagai jenis ekspresi kreatif, menciptakan pengalaman yang menarik dan mengubah cara kita melihat seni dalam konteks yang lebih luas. Diharapkan penelitian ini akan menjadi landasan untuk pengembangan lebih lanjut dalam bidang fotografi seni dan sastra, serta menginspirasi para seniman/peneliti untuk terus menggali batas-batas kreativitas dalam fotografi puisi.